Application of the Scale of Indicators of Suffering at Work and the perception of psychosocial risk factors by Occupational Safety Technicians (Research, Society and Development, 2025)
Objective: This article aimed to present the results of the application of the Occupational Distress Indicators Scale to Occupational Safety Technicians working in Brazil. Method: In this study, for data collection and quantitative analysis, the Occupational Distress Indicators Scale (EIST) was applied to 78 Occupational Safety Technicians, with 28 questions divided into 3 factors: meaning at work, mental exhaustion and recognition at work, a scale derived from the Protocol for the Assessment of Psychosocial Risks at Work. The Scale was formatted in the Google Forms tool and distributed to professionals from different regions of Brazil. Results: with the collection and analysis of the data, the results of the application of the Scale indicated mental exhaustion as the psychosocial risk factor with the greatest potential for suffering at work, with most of the items falling within the medium and borderline risk potential. In the final considerations, the perception of psychosocial risk factors as potential causes of suffering at work and a need for more scientific productions in the area of health and safety at work for a better mapping of the mental health of professionals working in the country were highlighted.